"AVESTA" - AS AN IMPORTANT SOURCE FOR STUDYING THE HISTORY OF UZBEKISTAN (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
This article leads to the conclusion that for thousands of years the Avesta religion has paid attention to social and moral problems. The main duty of a person is to fight evil, prescribed by the truth of faith; "good thought", "good word", "good deed". "Avesta" is a historical document, it testifies that in our ancient region there was a great state, a great state, great spirituality, great culture.